ANALISIS PERBANDINGAN RASIO SOLVABILITAS PT UNILEVER INDONESIA TBK BERDASARKAN LAPORAN KEUANGAN PERIODE 2024-2025 - Aeni Putri Andryansyah; Abbiegahlan Alief Al’ardie; Ardi Virmansyah; Cikal Elsa Dewi Rinjani; Angga Sanita Putra (CV. Denasya Smart Publisher, 2026)
Solvency ratio analysis is a method for evaluating the sustainable financial health of companies that are listed on the Indonesia Stock Exchange (IDX), particularly in the highly competitive Fast Moving Consumer Goods (FMCG) sector. This research examines the financial impact of a major corporate move by PT Unilever Indonesia Tbk (UNVR). In December 2025, UNVR sold its Ice Cream division for roughly IDR 7 trillion and used some of the funds to pay off IDR 1.45 trillion in bank loans. This study aims to analyze the company's financial stability between 2024 and 2025 by looking at the Debt to Equity Ratio (DER), Debt to Asset Ratio (DAR), Interest Coverage Ratio (ICR), and Long Term Debt to Equity Ratio (LTDER). The research relies on a quantitative descriptive method using 2025 annual financial data audited by KPMG. The findings indicate substantial improvements. The DER dropped from 6.47 to 3.47 times, while the DAR improved slightly from 0.87 to 0.78. The most significant improvement was seen in the LTDER, which plummeted from 0.96 to 0.29 times. Although the ICR decreased from 52.68 to 38.85 times, the company's ability to cover its interest payments remains incredibly safe. Overall, the sale of the Ice Cream business heavily boosted Unilever's financial strength by increasing its equity. However, the DAR remains above the generic 0.5 benchmark, showing that operational debts still make up a large portion of the company's financial structure and require steady management.